Manual de Procedimientos en al área de Orientación y Psicología, del Departamento de Vida Estudiantil y Servicios Académicos (DEVESA) del Tecnológico de Costa Rica, Sede Regional San Carlos - Bermúdez-García, Kevin Sebastián (Instituto Tecnológico de Costa Rica, 2015)
The following project consists of making a Manual of Procedures that agrees to increase the efficiency in the Administrative Management of the area of Orientation and Psychology of the DEVESA, Since the Department if it is not provided in these moments with the Manual one of Procedures for the area in specific. To be able to achieve the proposed main target, there is used a series of methodological mechanisms that allow the securing of the information of a best possible way, for which there is used a questionnaire of proper making, not holding a permit interviews, direct observation and also for the analysis of each of the procedures the “Hexámetro Quintiliano” will be used. As such there will be obtained a Manual of Procedures that includes the different processes in the field of Orientation and Psychology, properly documented and analyzed, allowing to offer a base so much for the current collaborators as future employers in the area, in addition to offering the recommendations that arise in search of a progress and continuous update for the area itself.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2015.
Keywords: Orientación y Psicología; Manual de procedimientos